Dari Hati ke Bumi: Merajut Empati Anti-Bullying dan Menumbuhkan Kepedulian Melalui Praktek Daur Ulang Sampah Anorganik di SD PEKAUMAN - Muhammad Ali Budiansyah; Agistya Ningsih Prasistiya; Orsela Dwi Ratnasari; Dea Adelia; Alya Mutiara Rohmah; Abrisam Fatih Junan; Nur Aini; Trapsila Siwi Hutami; Agung Nugroho Puspito (Jurnal Pengabdian Nasional (JPN) Indonesia, 2026)
Bullying in schools and low awareness of environmental conservation are two important issues that need to be addressed early on. UNESCO data (2019) shows that globally, nearly one in three students experience bullying. In Indonesia, the KPAI Survey (2022) noted an increase in bullying cases, with 51% occurring in elementary schools, indicating the urgency of early intervention. This activity evaluated the effectiveness of education in increasing students' knowledge about bullying prevention and their understanding and skills in recycling. Participatory methods such as interactive stories, simulations, and creative workshops involved 42 students. The evaluation results showed a significant improvement. A total of 85% of 3rd and 4th grade students were able to identify forms of bullying and how to deal with them. Meanwhile, 90% of students in grades 3 to 6 successfully created recycled products and their awareness of the importance of environmental cleanliness increased. The interactive and direct educational approach proved to be effective. The integration of these two topics into the school program is recommended to shape students' character to be socially and environmentally conscious in a sustainable manner.